Effect of seed oil Ricinus communis on E. coli isolated from Recurrent Urinary Tract Infections - Al-Kuraishi, Rania; Al-Shamma, Laith; Al-Mathkhury, Harith (Iraqi Journal of Science, 2024)
This study was conducted in Wasit governorate for the period between February 2012 to February 2013 to determine the impact of Castor seed oil at different concentrations 100, 75, 50 and 25% in inhibition of the growth of E. coli isolated from 52 male and female patients (2-70 yrs) attending Al Zahra Hospital and Al Karama Hospital in Kut city. Oil was extracted from seeds of Castor had the ability to inhibit E. coli isolated from patients presented with recurrent urinary tract infections . Zone of inhibition accomplishing was 9.06 mm in diameter.HPLC analysis revealed that the content of α-linolenic in Castor seed oil (18.90 μg\ml) was higher than other fatty acids followed by oleic. Perhaps this is why it able to inhibit E. coli; which affect the cellular components in bacteria.